1980
DOI: 10.1055/s-2007-1019613
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies of Manic-depressive lllness*

Abstract: The Unipolar (UP) and Bipolar (BP) forms of affective illness appear not to be genetically and physiologically identical, although the degree of overlap in family and biologic pharmacologic studies is considerable. It appears likely that at least a subgroup of UP illness shares its genetic diathesis with BP illness. The hypothesis of monoamine alterations associated with the affective illnesses has led to studies of genetics of enzymes of monoamine metabolism as observed in peripheral blood, erythrocyte catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Mit unserem Exkurs zu diesen sicher notwendigen Untersuchungen der zitierten Autoren sollte nur exemplifiziert werden, wie wenig derartige Ergebnisse geeignet sein können, die Entitätenlehre zu stützen. Es handelt sich hier um ein dankenswerterweise besonders gut belegtes Schulbeispiel für die Variationsmäglichkeiten von pathogenetisch prinzipiell einheitlichen psychischen Verfassungen, das uns anregen sollte, im Sinne von Gershon (1980) nach genetischen und anderweitigen biologischen Gründen für derartige phänotypische Auslenkungen zu suchen.…”
Section: Zur Typisierung Innerhalb Der Klassischen Psychosegruppenunclassified
“…Mit unserem Exkurs zu diesen sicher notwendigen Untersuchungen der zitierten Autoren sollte nur exemplifiziert werden, wie wenig derartige Ergebnisse geeignet sein können, die Entitätenlehre zu stützen. Es handelt sich hier um ein dankenswerterweise besonders gut belegtes Schulbeispiel für die Variationsmäglichkeiten von pathogenetisch prinzipiell einheitlichen psychischen Verfassungen, das uns anregen sollte, im Sinne von Gershon (1980) nach genetischen und anderweitigen biologischen Gründen für derartige phänotypische Auslenkungen zu suchen.…”
Section: Zur Typisierung Innerhalb Der Klassischen Psychosegruppenunclassified
“…At the same time, many classic genetic studies suggested that susceptibility to mood disorders consists of genetic features, common both to unipolar and bipolar disorders, and specific genetic factors for bipolar disorder [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic research occupies an important place in the studies directed at clarifying the aetiology of the endogenous psychoses [Gershon, 1980]. Besides analyses of family trees and epidemiological studies, attention is now being directed at marker, linkage, and association analyses.…”
mentioning
confidence: 99%